Physicochemical evaluation of blackberry wine (RUBUS GLAUCUS), made in Santa Rosa de Copán, Honduras - Torres Mejía, Juan Alexander; Torres Mejía, Fredy (Nexo Revista Científica, 2022)
A study was carried out on "Physicochemical, bromatological and sensory evaluation of artisanal blackberry wine (Rubus glaucus), made in the municipality of Santa Rosa de Copán, Honduras" with the purpose of developing a scientific and technical input that will help MSMEs (Micro, Small and Medium Enterprises) in the area, determine the organoleptic and sensory characteristics of artisanal blackberry wine produced in the Western Region of Honduras, establishing what is the incidence in consumer preferences, analyzing the demographic variables of the population or sample studied, also through the laboratory analysis prepared by the FHIA "Honduran Foundation for Agricultural Research", the bromatological qualities of artisanal blackberry wine were characterized, raw material from Belén Gualcho Ocotepeque, also sensory evaluation by expert tasters and sommelier the profile of the aged finished product, finally five (5) focus groups or cupping panel was organized, made up of 7 people to determine the sensory qualities by non-experts, initially they were trained in topics on the parameters to be evaluated in order that the evaluation carried out was carried out objectively.